Obravnavanje curka plinskega olja in nadomestnih goriv - Volmajer, Martin (Strojniški vestnik, 2004)
This paper presents numerical analyses of sprays of diesel and some alternative fuels. The fuel spray characteristics (the droplet size and the penetration length) of diesel fuel, biodiesel and waste cooking oil were calculated using the computational fluid dynamics program FIRE. Some of the characteristics were calculated using existing empirical models. The analyses were made for two different injection systems: direct and indirect injection. In the case of indirect injection, the results were also compared with fuel-spray photographs.
Keywords: vbrizgavanje goriva; olje plinsko; biodizel; olja odpadna; olja rastlinska; numerična analiza